Sweetness & lightning. 10 - Amagakure, Gido (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
Tsumugi's growing up fast, and the more she wants to do, the more complications Kohei has to deal with--from misunderstandings at school to the major milestone of Tsumugi's first bicycle. Kotori's life is getting busier, too, and it's not just because of her burgeoning ambitions: Her family situation may be about to change. But despite all the hustle and bustle of their lives, the delights of food and cooking (sukiyaki, udon, and more!) sustain all three.